Active Extension in a Foreland Trapped Between Two Contractional Chains: The South Apulia Fault System (SAFS). Issue 7 (7th July 2020) - Maesano, F. E.; Volpi, V.; Civile, D.; Basili, R.; Conti, A.; Tiberti, M. M.; Accettella, D.; Conte, R.; Zgur, F.; Rossi, G.
Abstract: The response of continental forelands to subduction and collision is a widely investigated topic in geodynamics. The deformation occurring within a foreland shared by two opposite‐verging chains, however, is uncommon and poorly understood. The Apulia Swell in the southern end of the Adria microplate (Africa‐Europe plate boundary, central Mediterranean Sea) represents one of these cases, as it is the common foreland of the SW verging Albanides‐Hellenides and the NE verging Southern Apennines merging into the SSE verging Calabrian Arc. We investigated the internal deformation of the Apulia Swell using multiscale geophysical data: multichannel seismic profiles recording up to 12‐s two‐way time (TWT) for a consistent image of the upper crust; high‐resolution multichannel seismic profiles, high‐resolution multibeam bathymetry, and CHIRP profiles acquired by R/V OGS Explora to constrain the Quaternary geological record. The results of our analyses characterize the geometry of the South Apulia Fault System (SAFS), a 100‐km‐long and 12‐km‐wide structure attesting an extensional (and possibly transtensional) response of the foreland to the two contractional fronts. The SAFS consists of two NW‐SE right‐stepping master faults and several secondary structures. The SAFS activity spans from the Early Pleistocene through the Holocene, as testified by the bathymetric and high‐resolution seismic data, with long‐term slip rates in the range of 0.2–0.4 mm/yr. Considering the position within an area with few or none other active faults in the surroundings, the dimension, and the activity rates, the SAFS can be a candidate causative fault of the 20 February 1743, M 6.7, earthquake. Key Points: The Apulia Swell, an offshore foreland enclosed between two contractional domains, is undergoing extension since the Early Pleistocene Extension in the Apulia Swell is accommodated by the South Apulia Fault System, a 100‐km‐long and 12‐km‐wide structure The South Apulia Fault System has a slip rate of 0.2–0.4 mm/yr and could have caused the 20 February 1743, magnitude 6.7, earthquake